Natural disasters as unique socioscientific events: Curricular responses to the New Zealand earthquakes - Rennie, Leonie; Wallace, J.; Venville, G. (2018)
© Springer International Publishing AG, part of Springer Nature 2018. This chapter examines earthquakes as a real-world, socioscientific issue to explore how schools, school curricula, school systems, and communities respond to the learning opportunities created by a natural disaster in the local or global community. We identified some of the issues that determine how different countries deal with earthquake preparation, response, and the factors that affect recovery. We then reviewed school-based, curriculum, and community responses to the Canterbury earthquakes in New Zealand as a case study. In the immediate aftermath, attention focused on the emotional support of students, teachers, and families, and efforts were made in combination with the community to return to normal schooling and curriculum stability in students' lives. We suggest that recovery from such natural disasters must be both flexible and integrated across curriculum and the community, drawing widely on available resources.